Firm Structural Traits and Stock Performance During and Post Covid-19 Pandemic - Samuel Ejiro Uwhejevwe-Togbolo; Prince Efanimjor; Tedlyn Akpevwe Etu; Nkechi Emeka-Nwokeji Emeka-Nwokeji; Joshua Kenechukwu Onuora (CV. Proaksara Global Transeduka, 2025)
The study examines the effect of firm structural traits on stock performance in a crisis period such as Covid-19 pandemic. The study assuages some firm structural traits to include profitability, firm size, firm leverage, business risk, asset structure, firm age, and market capitalization. While Stock performance is the ratio of each stock’s final price to its start price on each anniversary date. The study made use of the quantitative research which intends to adopt the use of a pairwise comparison method to examine the effect of firm structural traits on stock performance. The population of this study consisted of 108 non-financial firms (NFF) from the 10 sectors quoted firms on the floor of the Nigerian Exchange Group (NGX) with available and accessible annual reports that covered the study period of 2020, 2021, 2022 and 2023. The study acknowledged 2020-2021 as covid year, while 2022-2023 as post covid year. However, 82 firms were selected from the population of non-financial firms that existed during and post COVID-19 pandemic period. The statistical analysis to evaluate the relationship between independent and dependent variables was Generalized Method Moments (GMM) regression analysis. The findings suggest that profitability was a key factor in stabilizing stock prices during the crisis, but as the economy began to recover, other factors gained prominence, and profitability became less influential. The study concluded that during the pandemic, profitability (ROA) was crucial for stock performance, but its significance diminished post-pandemic. It was recommended in the study that firms should focus on maintaining strong profitability to stabilize stock prices. Post-pandemic, it is important to diversify focus beyond profitability as other factors may become more influential.